Adoption of ChatGPT in Higher Education: Insights from the Unified Theory of Acceptance and Use of Technology Model - Syahara Inda Wahdah; Riza Yonisa Kurniawan; Nico Irawan (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
Artificial Intelligence (AI) already emerged as a dominant and transformational strength in industry, research, academia, and business. ChatGPT is one example of Generative AI in education that can transform teaching methods and improve users' soft skills. The objective of this research to examine the factors in UTAUT 2 that drive ChatGPT adoption among students in higher education. Data were obtained from questionnaires distributed to 340 higher education students and then analysed using the PLS-SEM method. The results found that age-moderated performance expectations, gender-moderated effort expectations were shown to influence the behavioural intention of using ChatGPT on student learning. Likewise, social influence and habit. The results of this study are expected to add important insights for policy makers in higher education in developing AI technology adoption strategies in accordance with the development and needs of students, given that this is a newly introduced technology.